Three-dimensional reconstruction of a shooting crime scene - Yalçın, Nursel; Gençay, Pelin Su (Edelweiss Applied Science and Technology, 2024)
The crime scene is technically the place where an illegal act took place. The investigation first starts at the crime scene. Documentation of the crime scene is of great importance in order to make correct decisions in the investigation and prosecution stages, With the development of technology; the use of different devices and different technologies in crime scene investigation and crime scene documentation has created a new working area for many forensic scientists and law enforcement officers. Taking a general view of the crime scene without contamination, low margin of error in measurements can be shown as the main reasons for the use of laser scanning devices at the crime scene. A firearm crime scene was staged using different evidence. In the staged crime scene, a laser scanning device was also used along with the use of photography, sketching and note-taking methods from traditional documentation methods. In this study, the adequacy of the traditional methods alone, the adequacy of the laser scanning device alone, and the adequacy of the two methods together for reconstruction were discussed. The aim of this study is to determine the contributions and limitations of documenting the crime scene with a laser scanning device in combination with traditional documentation methods to the three-dimensional reconstruction of the crime scene.